Protocatechuic acid modulates reproductive dysfunction linked to furan exposure in rats (2020)
The reproductive toxicity associated with furan exposure in both animals and humans has been documented. Protocatechuic acid (PCA), a dietary polyphenolic chemical, reportedly elicits beneficial effects on the male reproductive system. However, the influence of PCA on the reproductive toxicity related to furan exposure is unavailable in the literature. The current study evaluated the effects of PCA on the dysfunctional reproductive axis caused by furan exposure in rats. Experimental animals were exposed to furan (8 mg/kg) or co-treated with furan (8 mg/kg) and PCA (25 or 50 mg/kg) for twenty-eight successive days. Results revealed that PCA treatment significantly alleviated furan-mediated declines in sperm production and characteristic qualities as well as in serum levels of prolactin, luteinizing hormone, follicle-stimulating hormone, and testosterone. Further, PCA attenuated furan-induced reduction in antioxidant enzyme activities and testicular function marker enzymes, namely lactate dehydrogenase, glucose-6-phosphate dehydrogenase, acid phosphatase, and alkaline phospha- tase. PCA effectively mitigated furan-mediated increases in myeloperoxidase activity, levels of reactive oxygen and nitrogen species, nitric oxide, tumour necrosis factor-alpha, and interleukin-1^ in testes, epididymis, and hypothalamus of rats. Moreover, PCA increased anti-inflammatory cytokine interleukin-10 but suppressed cas- pase-9 and caspase-3 activities and ameliorated injuries in the testes, epididymis, and hypothalamus of furan- treated rats. In conclusion, PCA ameliorated deficits in the hypothalamic-pituitary-gonadal axis function in furan-exposed rats by suppressing oxido-inflammatory stress and apoptosis.